HEAVY METAL ANALYSIS OF THE ERGENE RIVER, TURKEY - Koca, Sinan; Ozguven, Betul Oyku; Gurer, Azra; Dereli, Elif Nas; Ozer, Ecenaz; Benzet, Alper; Benzet, Arda; Aytekin, Erdener Tuna; Aygun, Umut Sarp; Can, Deniz; Basaran, Yaprak; Benzet, Hatice; et al. (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2021)
The Ergene River Basin, which endows from the Istiranca mountains, is one of the centers of industry in the Marmara region. The industrial busy area provides substantial clues about the anthropogenic effect of contamination. Nearly all industrial, domestic and agricultural wastewater is discharged directly or indirectly to the Ergene River. With this paper, nine students (9th and 10th class) from Kirklareli Science High School intervene in the discussion of heavy metals by taking samples from 13 different locations along the Ergene River with the leadership of the teacher. The points where the samples are taken are determined by the Ministry of Environment and Urbanization. All the steps in the study arc supervised by a scholar from Yildiz Technical University. The discussion commences with descriptive analysis, binary correlations and hierarchical cluster analysis of eight heavy metals. The discourse percentages of pollution of the three eigenvalues and the rotation matrix continue with linear modeling by clustering the variables. To more closely recognize the anthropogenic effect, the reader is presented with Contamination Factor (CF), Enrichment Factor (EF) and Pollution Load Index (PLI) values.
Keywords: Ergene River; Mathematical approach; Contamination factor; Enrichment factor; Pollution load index; COMPONENT ANALYSIS; SEDIMENTS; POLLUTION; ISTANBUL; CONTAMINATION; STREAM; BASIN; RISK; Environmental Sciences & Ecology